Comparison of two methods of erosive rains determination - STŘEDOVÁ, Hana; KRÁSA, Josef; ŠTĚPÁNEK, Petr; NOVOTNÝ, Ivan (Contributions to Geophysics and Geodesy, 2014)
Number of erosive rains, kinetic energy of erosive rains and factor of erosiveefficiency of rains according to the USLE methodology were assessed by two methodsof erosive rains determination. The first method (VAR1) defined erosive rains by intensity≥ 0.4 mm· min−1; total ≥ 12.5 mm and the second method (VAR2) by intensity≥ 6 mm· 15 min−1; total ≥ 12.5 mm. Database contained one minute precipitation datafrom four automatic stations in the Czech Republic for the period of 2000–2005. Two-wayanalysis of variance (ANOVA) showed a statistically highly significant difference betweenthe annual number of erosive rains determined by the two methods. The rains simultaneouslycomplying with two following criteria (30 min intensity lower than 15 mm·h−1 andsum of 40 mm) were not generally classified as erosive rains according to VAR2. The numberof erosive rains determined by VAR2 most often reached 40 to 50% of VAR1 results.Two-way ANOVA proved highly significant differences between the kinetic energy valuesfor the erosive rains determined by VAR1 a VAR2. According to VAR2 the rains withkinetic energy lower than 3 MJ/ha are generally not considered as erosive rains. Theresults of kinetic energy of the erosive rains determined by VAR2 most often reached 60to 70% of VAR1 results. Two-way ANOVA has not proved a statistical difference betweenannual values of R factor of erosive rains determined by the two methods. According toVAR2 the rains with R factor lower than 5 are in general not included into annual Rfactor value.The results of annual R factor values of erosive rains determined by VAR2are about 25% lower than the results of VAR1.